Characterization of motor and propeller sets for a small radio controlled aircraft - Mana Saedan (2018)
© 2015 IEEE. Electric motor and propeller selection is an important key in designing a radio controlled aircraft especially when designing a new type of aircraft. Since the characteristics of commercial RC electric motors and propellers are usually not reported, this paper hence demonstrates experiments to determine suitable pairs of motors and propellers that produces enough forces for an aircraft within constraints. The developed test bed utilized simple load cells to determine lifting forces and drag moments of propellers is presented. The investigated characteristics of motor/propeller including averaged lifting forces, averaged drag moments, maximum temperature of motors, and also input electrical current and power are reported.